Kajian Tafsir Ilmi atas Ayat-Ayat Al-Qur’an tentang Bencana Longsor (Studi Kasus : Cilowong, Banten) - Muhammad Ilham Wijaya Kusuma; Siska Adelia Zahra; Syaiful Rahman; Muhamad Jefri; Andi Rosa (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
This study examines landslide disasters through a scientific interpretation approach to the verses of the Qur'an, focusing on the landslide incident at the Cilowong Final Waste Disposal Site (TPSA), Banten. Landslide disasters are not only viewed as natural events, but also as a form of divine warning reflected in QS. Ar-Rum verse 41. This study was conducted using the thematic method (maudhu'i) and a qualitative approach through literature and documentation studies. The results of the study indicate that the verses of the Qur'an contain scientific signs that can be aligned with contemporary science, but still require a careful interpretation method so as not to deviate from their original meaning. The landslide case in Cilowong reflects the negative impacts of unwise environmental management and emphasizes the need for synergy between religious values ​​and scientific knowledge in disaster management efforts. This study emphasizes the importance of collective awareness in preserving nature while making the Qur'an a spiritual guide in understanding and responding to natural phenomena.